2020
DOI: 10.1021/acsnano.0c03694
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Molecular Charge Density Waves in Single-Layer-Thick Islands of a Dirac Fermion System

Abstract: Charge density waves have been intensely studied in inorganic materials such as transition metal dichalcogenides; however their counterpart in organic materials has yet to be explored in detail. Here we report the finding of robust two-dimensional charge density waves in molecular layers formed by α-(BEDT-TTF)2–I3 on a Ag(111) surface. Low-temperature scanning tunneling microscopy images of a multilayer thick α-(BEDT-TTF)2–I3 on a Ag(111) substrate reveal the coexistence of 5a 0 × 5a 0 and R9° charge density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We first focus on the exploration of the structure–property relationship based on materials imaging as a quantitative tool. Recent progress in high-resolution, real-space imaging techniques such as scanning probe microscopy (SPM) or AFM, , TEM, , scanning transmission electron microscopy (STEM), , scanning tunneling microscopy (STM), , and atom probe tomography (APT) has allowed the direct and efficient imaging of atomic columns and surface/interfacial atomic structures. These techniques enabled the direct visualization of the structure of materials, providing information on structural motifs that underlie crystals, grains, grain boundaries, dislocation cores, and quasicrystals, thereby leading to a fundamental understanding of the chemistry in these systems.…”
Section: Integration Of Structure–property and Processing–structure R...mentioning
confidence: 99%
“…We first focus on the exploration of the structure–property relationship based on materials imaging as a quantitative tool. Recent progress in high-resolution, real-space imaging techniques such as scanning probe microscopy (SPM) or AFM, , TEM, , scanning transmission electron microscopy (STEM), , scanning tunneling microscopy (STM), , and atom probe tomography (APT) has allowed the direct and efficient imaging of atomic columns and surface/interfacial atomic structures. These techniques enabled the direct visualization of the structure of materials, providing information on structural motifs that underlie crystals, grains, grain boundaries, dislocation cores, and quasicrystals, thereby leading to a fundamental understanding of the chemistry in these systems.…”
Section: Integration Of Structure–property and Processing–structure R...mentioning
confidence: 99%
“…The charge-density-wave (CDW) phase is a macroscopic quantum state consisting of a periodic modulation of the electronic charge density accompanied by a periodic distortion of the atomic lattice. The early work on CDW effects, performed with bulk samples of the quasi-one-dimensional (1D) metallic crystals, revealed many spectacular phenomena: nonlinear electron transport, oscillating electric current for constant voltages, giant dielectric response, and multistable conducting states. Recent years witnessed a rebirth of the field of CDW materials and devices, partially driven by an interest in layered quasi-2D van der Waals materials where CDW phases can manifest themselves at room temperature (RT) and above. The size and geometry of quasi-2D CDW films provide compelling opportunities for device fabrication. The early studies of de-pinning of CDWs in quasi-2D materials reported certain common features among CDW phenomena in quasi-1D and quasi-2D systems. , However, there is also an understanding of differences in physics governing CDW phases in material systems of different dimensionalities and crystal structures. , …”
mentioning
confidence: 99%
“…This means that individual cation and anion units in the complex maintain their own charges. Therefore, these ionic clusters are different from a class of materials known as donor–acceptor charge transfer complexes [ 21 , 22 , 23 ] where charge transfer from the donor to the acceptor molecules stabilizes the materials.…”
Section: Resultsmentioning
confidence: 99%